2010
DOI: 10.1253/circj.cj-10-0048
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Complex Fractionated Atrial Electrogram in the Electroanatomically Remodeled Left Atrium of Patients With Atrial Fibrillation

Abstract: Background: Complex fractionated atrial electrogram (CFAE) guided ablation is effective in some patients with persistent atrial fibrillation (PeAF), but the pattern of CFAE may be different in the remodeled left atrium (LA). Methods and Results:In 100 AF patients (83 males, 55.0±10.6 years old) with AF (51 paroxysmal AF (PAF), 49 PeAF) who underwent catheter ablation, CFAE cycle length (CL) and distribution (NavX 3D map) were compared according to the LA volume (3D-CT) and endocardial voltage (during high righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The settings included a refractory period of 40 ms, a peak-to-peak sensitivity between 0.05 mV and 0.1 mV, and a duration of 10 ms. Continuous CFAEs were defined as having a mean fractionation interval <50 ms and variable CFAEs as having a fractionation interval of 50 to 120 ms. [22][23][24] For fast-Fourier transform analysis, DF The bipolar signals obtained from the 5-second recording were analyzed, and the highest peak frequency of the resulting spectrum was identified as the DF. On the DF map produced by the NavX system, a high DF site was defined as a site with a frequency >8 Hz and colored bright purple.…”
Section: Cfae and Fast-fourier Transform Analysesmentioning
confidence: 99%
“…The settings included a refractory period of 40 ms, a peak-to-peak sensitivity between 0.05 mV and 0.1 mV, and a duration of 10 ms. Continuous CFAEs were defined as having a mean fractionation interval <50 ms and variable CFAEs as having a fractionation interval of 50 to 120 ms. [22][23][24] For fast-Fourier transform analysis, DF The bipolar signals obtained from the 5-second recording were analyzed, and the highest peak frequency of the resulting spectrum was identified as the DF. On the DF map produced by the NavX system, a high DF site was defined as a site with a frequency >8 Hz and colored bright purple.…”
Section: Cfae and Fast-fourier Transform Analysesmentioning
confidence: 99%
“…27 Electroanatomical remodeling of LA changes AF dynamics and the characteristics or distribution of complex fractionated atrial electrogram. 28 In this study, plasma concentration of TGF-β and EF were found to be related to the enlargement of LA volume. However, TGF-β might not be a sensitive predictor for the structural remodeling process in AF, because it was associated with enlargement of venous atrium or LAA those remodel at the later phase of LA remodeling.…”
Section: Discussionmentioning
confidence: 51%
“…CFAE regions are predominantly located at the septum, roof, and LA appendage (LAA) with low voltage surrounded by a high voltage area and low conduction velocity in patients with AF. CFAE cycle length was longer, and % area of CFAE was smaller in patients with an enlarged LA or low-voltage LA [34]. High plasma www.intechopen.com concentrations of TGF-beta and TIMP-1 had lower LA voltage and greater LA volume significantly in non-valvular AF patients [35].…”
Section: Clinical Implicationmentioning
confidence: 99%
“…However, this system has limitations in (i) distance problem, between catheter and tissue, decreased accuracy more than 34mm apart from tissue, (ii) signal-to-noise ratio problem, (iii) chamber size dependent, and (iv) virtual electrogram not real one, (v) inadequate substrate mapping and (vi) the associated moderate costs. Recently, an ultrasound-based 3D imaging modality, CARTO-based 3D ultrasound image system (Biosense Webster Inc., USA) has been developed to minimize merge process error [34]. The axial CT images were transferred to the electro-anatomic mapping system equipped with CARTO Merge image integration software (Biosense Webster).…”
Section: Non-contact Endocardial Mappingmentioning
confidence: 99%